Business models and bank performance: A long-term perspective - Mergaerts, Frederik; Vander Vennet, Rudi (Journal of Financial Stability, 2016)
This paper examines the effects of bank business models on performance and risk for a sample of 505 banks from 30 European countries over the period from 1998 to 2013. We document that business models in the European banking sector are characterized by a continuum, rather than a discrete set, of possible strategies. Using factor analysis to identify business models, we can account for this continuity. To estimate the impact of business models on performance, we use a methodology that is able to separate short-run effects from the longer-term impact of business model choices. Our findings show that retail-oriented banks perform better in terms of both profitability and stability and that diversification is associated with higher profitability. We report substantial variation of business model effects over different bank types. Our results lend support to the new capital regulations proposed in the Basel III framework, but we also argue that business model considerations should be more fundamentally integrated in the post-crisis regulatory and supervisory practice.